The role of Poly-ADP ribose polymerase (PARP) enzymes in chemotherapy-induced cognitive impairments – parallels with other neurodegenerative disorders - Ordaz, Dahlia A.; Gupta, Kalpna; Bota, Daniela A. (Frontiers in Pharmacology, 2025)
Poly (ADP-ribose) polymerase (PARP) enzymes are critical in repairing DNA damage induced by chemotherapy and/or radiation. Due to PARP’s role in DNA repair, inhibiting PARP leads to genomic instability and accumulation of damaged cells in cell cycle arrest. Previous studies have shown that PARP1 activation contributes to the development of various malignant disorders, and using PARP inhibitors is a promising intervention in these diseases. However, PARP activation is also common in neurological and inflammatory disorders. PARP inhibitors were studied in preclinical models of neurodegenerative disorders such as Parkinson’s, Huntington’s, and Alzheimer’s Disease (AD). In neurodegenerative disorders like AD, activated PARP1 induces Aβ and forms Tau tangles, worsening cognitive symptoms. PARP inhibitors are currently used in combination therapy with chemotherapy drugs, including cisplatin and temozolomide, which are all described as having significant rates of central and peripheral nervous system side-effects, raising the potential question of using PARP inhibition not only as a cancer treatment but as an approach to mitigate the toxicity of the cancer drugs. This review will summarize evidence for the potential use of PARP inhibitors for neurologic disorders and discuss future prospects of how PARP inhibitors could be repurposed as neuroprotective agents against the cognitive complications of chemotherapeutic drugs.